2018
DOI: 10.1002/adsc.201701474
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Electrophilic Trifluoromethylthiolation of Chiral Oxazolidinones: Access to Enantiopure α‐SCF3 Alcohols

Abstract: Lithium imide enolates featuring Evans' chiral oxazolidinone auxiliary were involved in diastereoselective a-trifluoromethylthiolation with electrophilic SCF 3 donors. Diastereopure products were isolated and converted to enantiopure a-SCF 3 alcohols without racemisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…[56] Studies related to the cleavage of the chirala uxiliary were also performed, and it was found that using LiOH/H 2 O 2 at 0 8C enantiomerically pure a-SCF 3 -substituted alcohols couldb eo btained withoutracemization. [56] Studies related to the cleavage of the chirala uxiliary were also performed, and it was found that using LiOH/H 2 O 2 at 0 8C enantiomerically pure a-SCF 3 -substituted alcohols couldb eo btained withoutracemization.…”
Section: Scheme30 Synthesis Of 3-(trifluoromethyl)thiochromonesmentioning
confidence: 99%
See 3 more Smart Citations
“…[56] Studies related to the cleavage of the chirala uxiliary were also performed, and it was found that using LiOH/H 2 O 2 at 0 8C enantiomerically pure a-SCF 3 -substituted alcohols couldb eo btained withoutracemization. [56] Studies related to the cleavage of the chirala uxiliary were also performed, and it was found that using LiOH/H 2 O 2 at 0 8C enantiomerically pure a-SCF 3 -substituted alcohols couldb eo btained withoutracemization.…”
Section: Scheme30 Synthesis Of 3-(trifluoromethyl)thiochromonesmentioning
confidence: 99%
“…[56] ChemCatChem 2018, 10,2717 -2733 www.chemcatchem.org 2018 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim center were obtained in excellenty ields with good to excellent enantioselectivities,w ithouti nfluence of the substitutions on the aromatic ring. Wynberg ion pair hydrogen bonding model.…”
Section: Scheme30 Synthesis Of 3-(trifluoromethyl)thiochromonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the direct introduction of a SCF 3 group onto amides, N ‐acyl oxazolidinones and ketones was also studied, albeit restricted to a handful of examples. [10h], …”
Section: Introductionmentioning
confidence: 99%